Determinants of entrepreneurial intention among economics students in can Tho City, Vietnam - Phan, Bao-Anh Ngoc; Cong, Hien Dinh (Edelweiss Applied Science and Technology, 2025)
This study investigates the determinants of entrepreneurial intention among economics students in Can Tho City, Vietnam. Drawing on an extended Theory of Planned Behavior model with seven factors, a quantitative study collected data from 300 final-year students via convenience sampling. Analysis using exploratory factor analysis and multiple linear regression revealed that all seven factors significantly influence entrepreneurial intention. Personal experience and perceived access to capital emerged as the strongest positive predictors, followed by entrepreneurial education, subjective norms, perceived supportive policies, attitude toward entrepreneurship, and perceived behavioral control. These findings underscore the crucial roles of practical exposure, financial access, and a supportive external environment (including policies and education) in fostering student entrepreneurship in Vietnam. The study contributes theoretically by extending the TPB in a Southeast Asian context and practically by offering guidance for universities and policymakers to design effective education programs and enhance the local entrepreneurial ecosystem, emphasizing practical experience, financial access, and policy support.